Therapy-Induced Neural Differentiation in Ewing's Sarcoma: A Case Report and Review of the Literature - Kıvılcım Eren ERDOĞAN; Mehmet Ali DEVECİ; Zeynep Ruken HAKKOYMAZ; Gülfiliz GÖNLÜŞEN (Federation of Turkish Pathology Societies, 2019)
Ewing's sarcoma (ES) is a small round cell tumor of adolescents or young adults that usually arises in the deep soft tissues of the extremities. The tumor cells have uniform round nuclei, fine powdery chromatin and indistinct nucleoli. CD99 (O13) is a product of the MIC 2 gene that is highly sensitive to ES but not specific. A panel of markers should be used for the differential diagnosis of small round cell tumors because nearly all others, on occasion, show membranous staining for CD99. One of the defining feature of ES is the presence of 22q12 gene rearrangement. The presented case is a 6 year-old boy complaining of swelling on his right leg. The biopsy was compatible with classic ES in terms of histopathological, immunohistochemical and cytogenetic criteria. Wide surgical resection was performed after chemotherapy. The posttreatment specimen was composed of uniformly small round cells mixed with areas of ganglion cells embedded in neurophil-like fibrillary background. Immunohistochemically, neoplastic cells revealed strong CD99 (O13) and NSE staining and the tumor had EWSR1 gene rearrangement. Morphologic alterations due to treatment are commonly seen in pediatric tumors. Single case reports have defined neural differentiation in ES but to the best of our knowledge this is the first report of ES in the literature with all histopathological, immunohistochemical, and cytogenetic criteria evaluated in both pretreatment and posttreatment specimens.